Pozitivni in negativni vidik ureditve družbeniške tožbe v delniški družbi v ZGD-1 in v AktG - Horvat Pogorelec, Mirjana (Podjetje in delo, 2014)
In this article the author is dealing with the institute of multilateral lawsuit - actio pro socio in Slovenian Companies Act (ZGD-1) and in German Aktiengesetz (AktG). The multilateral lawsuit actio pro socio enables the minority of shareholders to assert the compensation claims against management of a company when the company breaks the obligations connected with foundation of the company or with management of the business of the company and causes damage to the company. The multilateral lawsuit was introduced in the Slovene legislation with ZGD-1 in year 2006 and to AktG with the amendment UMAG. The multilateral lawsuit shall be brought by the minority of shareholders in their own name and for the account of the company.
Keywords: delničarji; delniške družbe; odgovornost; tožbe; vodenje